Distinct Spatial Patterns of SAR11, SAR86, and Actinobacteria Diversity along a Transect in the Ultra-oligotrophic South Pacific Ocean - West, Nyree J.; Lepère, Cécile; Manes, Carmem-Lara de O.; Catala, Philippe; Scanlan, David J.; Lebaron, Philippe (Frontiers in Microbiology, 2016)
Distinct distribution patterns of members of the major bacterial clades SAR11, SAR86 and Actinobacteria were observed across a transect from the Marquesas islands through the ultra-oligotrophic South Pacific Gyre into the Chilean upwelling using 16S rRNA gene sequencing and RNA-DNA fingerprinting. Three different Actinobacteria sequence clusters belonging to "Candidatus Actinomarinidae" were localised in the western half of the transect, one was limited to the gyre deep chlorophyll maximum and sequences affiliated to the OCS155 clade were unique to the upwelling. The structure of the surface bacterial community was highly correlated with water mass and remained similar across the whole central gyre (1300 nautical miles). The surface hyperoligotrophic gyre was dominated (>70% of all sequences) by highly diverse SAR11 and SAR86 operational taxonomic units and these communities were significantly different from those in the deep chlorophyll maximum. Analysis of 16S rRNA fingerprints generated from RNA allowed insights into the potential activity of assigned bacterial groups. SAR11 and Prochlorococcus showed the highest potential activity in all water masses except for the upwelling, accounting together for 65% of the total bacterial 16S rRNA in the gyre surface waters in equal proportions whereas the contribution of SAR11 decreased significantly at the deep chlorophyll maximum.